Local Spiritual Belief: Creative Posture of Mask Dancer-Maker in Malang of East Java Province - Robby Hidajat; Guntur (Anastasis: Research in Medieval Culture and Art, 2023)
This article discusses the creative posture of dancer mask makers in Malang of East Java Province. The ethnographic approach is chosen as a research method to obtain a description of the subject of the study. In the analysis process, the data are set into categories and interpreted. The result of the research shows that the creative process behind mask-making involves several stages. The first stage is wiwit, the building of commitment to maskmaking. The second stage is mbakali, the drafting of the mask. The third stage is maesi, the carving of face and crown shapes on the mask. Finally, the fourth stage is telasan, the finishing of the mask. The mask-making is a creative posture shown by artisans to produce artwork to be used as dance equipment in a mask puppet show. The Malang mask artisans do not differ from wooden mask artisans in other regions in terms of materials and technique. Their maskmaking process similarly involves wood as raw material, a knife as a carving tool, and slivering technique. Their mask-making skills are mostly inherited. The artisans surprisingly do not get their skills from internships but from watching, giving attention, and imitating other artisans. The creative posture is always based on local wisdom and orienting toward local spiritual beliefs. The effect of local spirituality can be found in material selection, carving techniques, and coloring patterns. The experience of mask artisans in putting local spirituality into the mask-making process needs to be reviewed.